Association between TyG related parameters and metabolic dysfunction associated fatty liver disease among nondiabetic individuals - Qian Zhang; Zhilong Liu; Jiaqi Zhang; Shangjie Yang; Liping Liu (Scientific Reports)
Abstract Metabolic dysfunction associated fatty liver disease (MAFLD) is a prevalent liver condition and presents a major clinical and public health problem worldwide. TyG index and its related parameters TyG-WHtR, TyG-WC and TyG-BMI have been proven to label insulin resistance reliably, which makes it an important parameter to reflect the composition and health status of human body. Recent studies in the general population have demonstrated that there exists a correlation between elevated TyG index and the development of MAFLD, but in the nondiabetic US population, this correlation remains unclear. We included 945 nondiabetic adult participants from NHANES 2017–2020 cycle in this cross-sectional study. To find the relationship that exists between TyG, TyG-WHtR, TyG-WC, TyG-BMI, HOMA-IR, QUICKI and the risk of MAFLD, we used four conventional multivariate adjusted logistic regression models, plotted the RCSs to conduct this study, analyzed the thresholds using a two-stage logistic model. We performed stratified and interaction analyses to identify whether the relationships were stable in different subgroups. Moreover, we assessed the predictive ability of these parameters for MAFLD by plotting ROCs. We found that there was a positive correlation between TyG index and the incidence of MAFLD as well as its related parameters in the nondiabetic population.